Aktivitas Antijamur Air Perasan Daun Seledri (Apium graveolens L.) Terhadap Candida albicans Secara In Vitro - Patra Inova Ardelia; Fauzia Andrini; M Yulis Hamidy (Fakultas Kedokteran Universitas Riau, 2010)
Celery (Apium graveolens L.) has been known as traditional medicine. Apigenin is one of active component in Celeryleaf that has fungicidal activity, so celery leaf’s extortion suspected has fungicidal activity to Candida albicans. Apigenincan solved in water. The aim of this research was to know antifungal activity of celery leaf’s extortion againsts Candidaalbicans in vitro.This is a laboratory experimental research by using completely randomized design and disc diffusion method. Celeryleaf’s extortion was divided into 3 concentrations, there were 25%, 50% and 100%. Ketoconazole 2% was used aspositive control and aquadest as negative control. The result of this research was based on analysis of variance, therewas significant difference between minimal 2 treatment (p=0.000) and confirmed with Post Hoc test, there were significantdifference in all treatments. As the conclusion, celery leaf’s extortion had antifungal activity againsts Candida albicansin vitro with the best concentration 50% but smaller than ketoconazole 2%.